The Effectiveness of Substitution Fine Aggregate by Pacitan Coral Sand to the Compressive Strength of Concrete - Devi, Rida Handiana; Safarizki, Hendramawat Aski; Putra, Imam Prasetyo Azhari; Marwahyudi, Marwahyudi (Science and Technology Research Centre, Universitas PGRI Semarang, 2023)
The south Pacitan district's coastal area in Indonesia has become a tourist place because of the more beach with captivating coral. However, that area's natural resources have not altered the function of construction material. Many research uses the coral reef to admixture concrete material in other countries that affect compressive strength. In this research, the coral reef from Pacitan modified the original dimension of fine aggregate for material substitute o to become the coral sand of fine aggregate with the different material characteristics from other coastal areas. The sample variation was created into four categories, and five samples in every category were concrete without coral sand or 0% coral sand content, 75% with coral sand, 85% with coral sand, and 90% with coral sand. All samples were tested when the concrete age was achieved 28 days after immersing for 14 days, so the concrete was in the maximum setting time condition. The result shows that the percentage effectiveness of coral sand content is 75% as fine aggregate substitution by increasing the compressive is 15.24%, however higher coral sand content causes the decrease until 27.12% to concrete without coral sand, this result can effect by the material characteristic of coral sand when changing the dimension